Synergistic muscle coordination of the Paralympic wheelchair tennis champion - Hakariya, N.; Murakami, T.; Kaneko, N.; Nakazawa, K. (Frontiers in Sports and Active Living, 2025)
Introduction: This study aimed to elucidate specific muscle coordination patterns in a Paralympic gold medal wheelchair tennis player. Recent neuroscience has proposed the concept of the "Paralympic brain", referring to use-dependent and impairment-specific plasticity observed in some Paralympians. Although the present study does not directly assess neural reorganization, this framework provides context for interpreting motor coordination strategies. Methods: We applied muscle synergy analysis of electromyographic (EMG) activities during the tennis serve to quantify muscle coordination in two male players: one a Paralympic and world champion (P1; osteosarcoma with hip and abdominal resections), and the other nationally ranked sub-elite player (P2; spina bifida with paralysis of the lower limbs and trunk). EMGs from 14 muscles and high-speed video were recorded during three flat serves. Results: Serve velocity was markedly higher in P1 (167 ± 11.3 km/h) than P2 (80.0 ± 8.9 km/h). Four synergies were identified in P1 and three in P2. A specific synergy (Syn1), dominant in the early takeback phase and involving lower trapezius and triceps brachii, was found only in P1 and may contribute to greater trunk rotation and serve velocity. In addition, the sparseness of muscle synergies was also higher in P1 than in P2. Discussion: These results indicate that elite serve performance is supported not only by muscular strength but also on specialized neuromuscular coordination strategies optimizing trunk rotation and energy transfer. They may be consistent with broader ideas of use-dependent and impairment-related adaptation described in the "Paralympic brain" framework. This study provides new insights into adapted motor strategies in Paralympic sport, underscoring the role of trunk control and residual function as key factors in training and performance optimization.